2020
DOI: 10.1097/phm.0000000000001588
|View full text |Cite
|
Sign up to set email alerts
|

Association Between FokI Polymorphism of Vitamin D Receptor Gene and Lumbar Spine Disc Degeneration

Abstract: Objective The aim of the present meta-analysis was to explore the association between FokI polymorphism of the vitamin D receptor gene and lumbar spine disc degeneration. Design The search was performed in PubMed, Scopus, and Web of Science databases up to January 2020. The authors selected nine studies comprising a total of 1549 cases and 1672 controls. The association analysis included the allelic, dominant, recessive, homozygous, and heterozygous gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…They concluded that FokI polymorphisms are linked with the elevated risk of IDD, including LDH, among Caucasians but not among the Asian population[9]. Another meta-analysis of Castillo-Avila et al, including 1,549 patients and 1,672 controls, indicated a statistically significant correlation between FokI polymorphisms and IDD[26]. Lan et al suggested that VDR mutations might hinder vitamin D metabolism, leading to the modulation of autophagy and the progression of IDD.…”
mentioning
confidence: 99%
“…They concluded that FokI polymorphisms are linked with the elevated risk of IDD, including LDH, among Caucasians but not among the Asian population[9]. Another meta-analysis of Castillo-Avila et al, including 1,549 patients and 1,672 controls, indicated a statistically significant correlation between FokI polymorphisms and IDD[26]. Lan et al suggested that VDR mutations might hinder vitamin D metabolism, leading to the modulation of autophagy and the progression of IDD.…”
mentioning
confidence: 99%